Evidence for a contact between glutamine-18 of lac repressor and base pair 7 of lac operator. - Ebright, R H (1986)
Glutamine-18 of the lac repressor (lacR) has been substituted by glycine, by serine, and by leucine. The specificities of wild-type lacR and of the three substituted lacR variants have been analyzed with respect to base pairs 5, 6, 7, 8, 9, and 10 of the lac operator (lacO). The data indicate that [Gly18]lacR, [Ser18]lacR, and [Leu18]lacR lose the ability to distinguish between the O+ base pair G . C and the Oc base pairs T . A and A . T at position 7 of lacO (KdOc/KdO+ approximately equal to 1). In contrast, the three substituted variants retain the ability to discriminate O+ from Oc at each other position, by factors of 9 to 37. Therefore, I propose that glutamine-18 contacts base pair 7 of lacO. These data suggest that the interaction between the helix-turn-helix motif and DNA may be very similar or identical in lacR and the catabolite gene activator protein.